Antimicrobial activity and phytochemical characterization of Carya illinoensis. (March 2017) - Bottari, Nathieli Bianchin; Lopes, Leonardo Quintana Soares; Pizzuti, Kauana; Filippi dos Santos Alves, Camilla; Corrêa, Marcos Saldanha; Bolzan, Leandro Perger; Zago, Adriana; de Almeida Vaucher, Rodrigo; Boligon, Aline Augusti; Giongo, Janice Luehring; Baldissera, Matheus Dellaméa; Santos, Roberto Christ Vianna
Abstract: Carya illinoensis is a widespread species, belonging to the Juglandaceae family, commonly known as Pecan. Popularly, the leaves have been used in the treatment of smoking as a hypoglycemic, cleansing, astringent, keratolytic, antioxidant, and antimicrobial agent. The following research aimed to identify for the first time the phytochemical compounds present in the leaves of C. illinoensis and carry out the determination of antimicrobial activity of aqueous and ethanolic extracts. The antimicrobial activity was tested against 20 microorganisms by determining the minimum inhibitory concentration (MIC). Phenolic acids (gallic acid and ellagic acid), flavonoids (rutin), and tannins (catechins and epicatechins) were identified by HPLC-DAD and may be partially responsible for the antimicrobial activity against Gram-positive, Gram-negative, and yeast. The results showed MIC values between 25 mg/mL and 0.78 mg/mL. The extracts were also able to inhibit the production of germ tubes by Candida albicans . Highlights: This study identified for the first time the phytochemical compounds present in the leaves of Carya illinoensis . Phenolic acids (gallic acid and ellagic acid), flavonoids (rutin), and tannins (catechins and epicatechins) were identified by HPLC-DAD. C. illinoensis presents important antimicrobial activity against 20 tested microorganisms. The results showed MIC values between 25 mg/mL and 0.78 mg/mL. The extracts were also able to inhibit the production of germ tubes by Candida albicans.